Kurikulum Pendidikan Islam: Landasan Dan Implementasi - Ramadhan, Surya; Elfizar, Nur Ikhsan; Khair, Faturrahman (Journal of Sustainable Education, 2025)
This study aims to determine the development and implementation of the Islamic education curriculum in Indonesia and to understand the challenges faced in its implementation. The method used in this study is a qualitative study with a descriptive analytical approach through a literature review of various curriculum documents, Islamic education literature, and government policies related to Islamic education. The results of the study indicate that the Islamic education curriculum in Indonesia has undergone several stages of development, starting from the traditional period in Islamic boarding schools to the integration of the national curriculum in the modern era. The current curriculum emphasizes character building, religious moderation, and integration between religious knowledge and general knowledge. However, the implementation of the curriculum still faces obstacles such as the quality of human resources, differences between regions, and limited educational facilities. Therefore, it is necessary to strengthen policies, improve teacher competence, and evaluate the curriculum on an ongoing basis so that Islamic education in Indonesia can run effectively and relevantly to the times.